Exploring the Legend of Sarip Tambak Oso: Development and Practicality Testing of an Interactive E-Module for Indonesian Language Instruction in Elementary Schools - Yunia Dwi Arini; Hendratno; Nurul Istiq'faroh; Mujahidin Farid (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
This study aims to examine the practicality of an interactive e-module based on the Legend of Sarip Tambak Oso as a teaching material for the Indonesian language for sixth-grade elementary school students, specifically in the learning of the analysis of the intrinsic elements of fictional stories. The focus of the study lies on the level of practicality of the e-module’s use from the perspectives of both teachers and students. The novelty of this study lies in the integration of the local legend of Sarip Tambak Oso as content in the interactive e-module, which provides contextual learning based on local wisdom, a departure from typical e-modules that tend to use generic content. The method used was research and development (R&D) based on the ADDIE model. A limited practicality test was conducted with 1 teacher and 22 sixth-grade students at SDN Kalisampurno 1 using a four-point Likert scale questionnaire, and the data were analyzed using quantitative descriptive methods. The results showed a practicality level of 91.25% (teacher) and 87.9% (students), both falling into the “very practical” category. This indicates that the e-module is easy to use, engaging, and supports interactive learning. Furthermore, the inclusion of local legends has the potential to strengthen students’ understanding of local wisdom. Thus, this e-module demonstrated a very high level of practicality in the limited pilot test and can serve as an alternative contextual teaching material for Indonesian language instruction in elementary schools.